The Occurrence of Myxomycete Communities in Taxodium distichum Forests: Influence of Substrates and Seasons - Yajing Chen; Wenlong Song; Gu Rao; Qun Dai; Shuzhen Yan; Shuanglin Chen (Microorganisms)
Myxomycete communities in Taxodium distichum forests and the influence of substrates and seasons on myxomycete diversity were studied. In total, 80 substrates (40 living barks and 40 litters) were collected from the sample site in winter, spring, summer and autumn of 2023, followed by moist chamber cultures. A total of 733 records representing 34 myxomycete species in 21 genera were obtained. Arcyria cinerea and six other species were abundant (A). Six species were common (C), six species were occasional (O), and fifteen species were rare (R). Species diversity (H’ = 2.04 ± 0.20) of corticolous communities was significantly higher than that (H’ = 1.49 ± 0.31) of litter-inhabiting communities (p < 0.05). Nonmetric Multidimensional Scaling (NMDS) analyses showed significant differences between these two communities (p < 0.01). Species diversity was slightly higher in summer and autumn compared to winter and spring. NMDS analyses indicated no significant differences among seasonal communities. Redundancy Analysis showed that the corticolous species were closely related to wind speed (p < 0.05), while litter-inhabiting species were mainly determined by temperature (p < 0.05). The study revealed that substrates and seasons influenced myxomycete communities in T. distichum forests, with the communities being particularly affected by the substrates in which they live.